ISOLASI DAN SELEKSI BAKTERI ASAM LAKTAT PENGHASIL PROTEASE DARI KOTORAN LUWAK (Paradoxurus hermaphroditus) - , ROSYIDA ISMI BARROROH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The scarcity of luwak (Paradoxurus hermaphroditus) and the limited capacity of digestive system has resulted in the limited production of luwak coffee. One of alternative system for luwak coffee production is employing an in vitro fermentation to mimic the natural fermentation system within the digestive system of luwak. A study has been carried out isolate microorganisms which may involve in natural fermentation of luwak coffee. The study was focused on obtaining lactic acid and proteolytic bacteria. The isolation was carried out by using Nutrient Agar and MRS agar followed by selection using CaCO 3 -enriched MRS agar and skim milk. The result of this study showed that 36 isolates out of total 93 isolates demonstrated the acid production and proteolytic ability. Fifteen isolates out of 36 isolates produce lactic acid homofermentatively and produced protease. Similarity analysis by using RFLP-PCR resulted in 4 groups of bacteria. The first group that includes bacteria with 100% similarity were: KLLAB.04